Stories of Re-Reading: Inviting Students to Reflect on Their Emotional Responses to Fiction - Brenda Daly (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
Although most literature courses teach students to focus on textual analysis, this essay argues that students should be given opportunities for exploring their emotional responses to the text.